Effects of the Oncoprotein PAX3-FOXO1 on Modulation of Exosomes Function and Protein Content: Implications on Oxidative Stress Protection and Enhanced Plasticity - Fahs, Assil; Ramadan, Farah; Ghamloush, Farah; Ayoub, Abeer J.; Ahmad, Fatima Ali; Kobeissy, Firas; Mechref, Yehia; Zhao, Jingfu; Zhu, Rui; Hussein, Nader; Saab, Raya; Ghayad, Sandra E. (Frontiers in Oncology, 2020)
Rhabdomyosarcoma (RMS) is a highly malignant soft tissue sarcoma classified into two major histologic subtypes: embryonal (ERMS) and alveolar (ARMS). ARMS subtype is clinically more aggressive, and characterized by an oncogenic fusion protein PAX3-FOXO1 (P3F) that drives oncogenic cellular properties. To understand the role of the fusion oncoprotein in paracrine signaling, we focused on secreted exosomes, which have been demonstrated to contribute to metastasis in multiple tumor types. Advanced Proteomics-bioinformatics analysis of the protein cargo of exosomes isolated from C2C12 myoblasts transduced with P3F fusion gene revealed 52 deregulated proteins compared to control cells, with 26 enriched and 26 depleted proteins. Using both PANTHER gene classification and Ingenuity Pathway Analysis (IPA) software, we found that the main biological processes in which the 52 deregulated proteins are involved, include “catalytic activity”, “binding”, “metabolic process” and “cellular process”. The pathways engaging the 26 enriched proteins include the “14-3-3 mediated signaling”, “cell cycle” and “ERK5, VEGF, IGF1and p70S6K signaling”. Furthermore, the main nodes in which deregulated exosome proteins and miRNAs intersected revealed pathways conferring protection from stress and promoting plasticity. Based on the bioinformatics analysis and the altered exososme proteome profile, we performed biochemical functional analysis to study the diverse properties of these exosomes where angiogenesis, stemness, and anti-oxidative stress properties were validated using different platforms. PAX3-FOXO1-modulated exosomes activated ERK, 4-EBP1 and MMP-2 in recipient cells, and enhanced angiogenesis and stemness. In addition, PAX3-FOXO1 led to lower cellular ROS levels and enhanced resistance against oxidative stress; and treatment of stromal cells with PAX3-FOXO1-modulated exosomes also conferred protection against exogenous oxidative stress. Our findings highlight the role of P3F fusion protein in modulating exosome cargo to confer a protective effect on recipient cells against oxidative stress and to promote plasticity and survival, potentially contributing to the known aggressive phenotype of the fusion gene-positive subtype of RMS.